Pengaruh Kualitas Sumber Daya Manusia dan Penggunaan Informasi Akuntansi Terhadap Keberhasilan Usaha dengan Ketidakpastian Lingkungan sebagai variabel moderating pada UKM di kota Medan - Sua Betria Dhani; Eka Nurmala Sari; Maya Sari (Economic Reviews Journal, 2024)
This study aims to determine the effect of the quality of human resources and the use of accounting information on business success with environmental uncertainty as a moderating variable in SMEs in the city of Medan. This type of research is quantitative with an associative approach. This research was conducted using a survey method by distributing questionnaires to SMEs in the city of Medan. The sampling technique in this study used a purposive sampling technique found in non-probability sampling with a total sample of 100 respondents. The data were analyzed using the partial least squares (SEM-PLS) structural equation model. The results of this study indicate that the quality of human resources affects business success and the use of accounting information affects business success. In addition, this study also finds that environmental uncertainty cannot moderate the quality of human resources on business success and environmental uncertainty cannot moderate the use of accounting information on business success.